Conscientiousness and Medication Adherence: A Meta-analysis. Issue 1 (20th June 2013) - Molloy, G. J.; O'Carroll, R. E.; Ferguson, E.
Abstract: Background: Approximately a quarter to a half of all people fail to take their medication regimen as prescribed (i.e. non-adherence). Conscientiousness, from the five-factor model of personality, has been positively linked to adherence to medications in several recent studies. Purpose: This study aimed to systematically estimate the strength and variability of this association across multiple published articles and to identify moderators of this relationship. Method: A literature search identified 16 studies ( N  = 3, 476) that met the study eligibility criteria. Estimates of effect sizes ( r ) obtained in these studies were meta-analysed. Results: Overall, a higher level of conscientiousness was associated with better medication adherence ( r  = 0.15; 95 % CI, 0.09, 0.21). Associations were significantly stronger in younger samples ( r  = 0.26, 95 % CI, 0.17, 0.34; k  = 7). Conclusion: The small association between conscientiousness and medication adherence may have clinical significance in contexts where small differences in adherence result in clinically important effects.